2004
DOI: 10.1111/j.1399-0012.2004.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent dipstick haematuria following renal transplantation

Abstract: Despite widespread testing for dipstick haematuria following renal transplantation, there are no published series describing the prevalence and possible causes of this complication in an adult population. A cross-sectional study of 640 renal transplant recipients under review at our follow-up clinic was performed. Persistent haematuria was defined as a minimum of 1+ of blood on urinalysis stick testing detected at not fewer than 75% of clinic visits since its onset, or since the start of routine testing, prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…Persistent microscopic hematuria, on the other hand, is often the earliest marker of recurrent IgAN, but it does not predict a poor outcome. [ 38 39 ] In evaluating the predictors of early graft failure in the posttransplant IgAN group, we found contrasting findings to that of the previous studies. The only significant predictor of early graft failure in our study was serum creatinine at 5 years.…”
Section: Discussioncontrasting
confidence: 56%
“…Persistent microscopic hematuria, on the other hand, is often the earliest marker of recurrent IgAN, but it does not predict a poor outcome. [ 38 39 ] In evaluating the predictors of early graft failure in the posttransplant IgAN group, we found contrasting findings to that of the previous studies. The only significant predictor of early graft failure in our study was serum creatinine at 5 years.…”
Section: Discussioncontrasting
confidence: 56%
“…Only few reports describing the frequency and possible causes of haematuria following kidney transplantation have been published in the literature [1][2][3]. In contrast to the previous reports, in which a majority of causes identified were associated with nonmalignant conditions, the most prevalent cause contributing to persistent haematuria in our series was urological malignancy (42.2%) including one superficial bladder UC, one invasive bladder UC, 16 patients with upper urinary tract UC (ureter/renal pelvis) and one adenocarcinoma of urachus.…”
Section: Discussionmentioning
confidence: 99%
“…Allograft renal cell carcinoma was diagnosed in one patient and was managed with partial graft nephrectomy. In addition, they concluded that patients with haematuria had poorer graft function and higher risk to progress to graft failure [3].…”
Section: Introductionmentioning
confidence: 99%
“…3 One of the most common causes of the posttransplant gross hematuria is related to the native kidneys and usually presents as the late onset posttransplant gross hematuria. Early onset posttransplant gross hematuria is usually caused by bleeding from the site of ureteroneocystostomy that is managed by conservative therapy and continues bladder irrigation.…”
Section: Discussionmentioning
confidence: 99%